THE INFLUENCE OF MAQASID AL-SHARIAH ON SUSTAINABLE INVESTMENT DECISIONS IN ISLAMIC FINANCE - Hotman, Hotman; Luthfi, M (Economics Studies and Banking Journal (DEMAND), 2025)
Islamic finance is increasingly developing with an emphasis on sustainability, but the integration of Maqasid principles al-Shariah in sustainable investment decisions remains underexplored. This research aims to fill this gap by analyzing the influence of Maqasid al-Shariah on sustainable investment decisions in the context of Islamic finance. This research aims to explore how the principles of Maqasid al-Shariah can be used as guidelines in making investment decisions that are not only financially profitable but also consider social and environmental aspects. This research uses a Systematic Literature Review (SLR) approach by collecting and analyzing relevant articles from the Scopus and Web of Science databases. Inclusion and exclusion criteria were applied to ensure the quality and relevance of the analyzed articles. The findings show that the integration of Maqasid al-Shariah in sustainable investment decisions can increase positive impacts on society and the environment, and support the achievement of sustainable development goals. This research also identifies challenges in implementing these principles. These findings make a significant contribution to the Islamic finance literature by highlighting the importance of Maqasid al-Shariah in sustainable investment practices, as well as offering guidance for Islamic financial institutions to develop more inclusive and sustainable products.